Parasites control on dairy farming at SÃ£o Paulo state - CecÃlia JosÃ© VerÃssimo; Flavia Vasques; Valdinei Tadeu Paulino; Keila Maria Roncato Duarte (Boletim de Indústria Animal, 2015)
The dairy cattle farming have a great importance on the economy and social aspects of São Paulo State. The parasites can reduce milk productivity, specially the cattle tick, Rhipicephalus (Boophilus) microplus. This work consisted on a survey on 40 dairy farms located in the Northeast region of São Paulo State. The principal objective of the quiz was to know how producers do the cattle tick control and about others parasites. 45% responded that the cattle tick is a problem in their properties and 65% were satisfied with the tick control, but only 17.5% know the biological cicle of this tick. The percentage of 29.5 was associated the hematologic diseases (anaplasmosis and babesiosis) with damages caused by the cattle tick, as well as 21.5% associated with the presence of screwworm (Cochliomiya hominivorax). The other responces about damages associated with the cattle tick were: weight loss (19.5%), milk loss (15.5%), mortality (12%) and transmission of others diseases (2%). The summer was the great response (88%) about the period of major tick incidence. The percentage of 87.5 of the surveyed applied acaricide with high frequency (7 to 30 days), but 50% apply selectively to the most infested cattle. The dairy workers (55%) and the owners (45%) apply the acaricide, always when they see tick infestation (92.5%) and the application is on all the animals’ body (87.5%) instead of parts of the body where it has more tick (12.5%). Only 7.5% answered they follow a strategic control, because the majority (75%) didn’t know a strategic tick control. In 41% of the properties the form of acaricide application was in spray, 90% using a costal pump and 10% an eletric pump. Others forms of acaricide application were injectable products (34%) and pour on (25%). The percentage of 77.5 does not contain the animals to make a correct acaricide application and only 12.5% use personal protective equipment. The acaricide product is chosen mainly by a technician indication (55%) followed by the store clerk (32.5%). Nobody chose the acaricide based on a test of effectiveness, because only 10% know the test and had used it. 40% said they know about the test but had never used and 50% never heard about the test. 95% are informed about tick resistance to the acaricides, the majority (32%) in courses and lectures, and 19% with others producers. And 62.5% changes the acaricide product when it is no more effective and 20% at each application. Fifty-five percent (55%) uses an endectocide for the cattle tick control and 44.5%, twice a year (generally with the foot and mouth disease vaccination in the months of may and november), but 28% use the endectocide six times a year, and 11%, monthly. The total deworm their animals, 62.5% twice a year. When the injectable or pour on product is applied, the cattle weight is estimated by visual estimation (100%) for calculating the dose of the drug. Only 40% consider the vesting of the product for disposing milk. Only 12.5% use an alternative to the cattle tick control, and of those, 60% use homeopathy. The percentage of 92.5 notice the presence of some natural enemy, being 100% birds, like egrets, chickens and others birds. Sixty-five percent (65%) controls Haematobia irritans infestation but none do Dermatobia hominis control. 40% has trouble with Cochliomiya hominivorax and none with other ticks. Only 25% has problem with coccidiosis. The result of the survey indicates that many points about the cattle tick control have to be worked with the producers, and the knowledge have to be passed to the technicians because 92.5% of these producers have technical assistance, being 70% frequent and 22.5% occasional assistance; only 7.5% have no technical assistance.